(untitled) (Journal of EAHIL, 2019)
The arts offer a broad range of historically-documented benefits to mental, physical and social health. UK-based charity Paintings in Hospitals was a pioneer of the modern “arts in health” movement and has provided arts services to willing healthcare partners for 60 years. Despite a large and continually-growing body of clinical evidence supporting the health benefits of the arts, and a recent parliamentary report suggesting that the arts could alleviate structural and financial stresses on health and social care services, resistance to nationwide integration of the arts with healthcare remains. The majority of this resistance stems from misunderstanding and misinformation that must be properly addressed before the “arts in health” sector is able to fulfil its potential.